1973
DOI: 10.1021/jo00942a022
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopropylamines as intermediates in a new method for alkylation of aldehydes and ketones

Abstract: All inorganic compounds used (perchloric acid, sodium perchlorate, sodium bromide, bromine) were reagent grade. Water used as solvent was distilled twice over alkaline potassium permanganate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…35,36 As amines, they are also susceptible to undergo single-electron oxidation at the lone pair of the nitrogen atom, which triggers cleavage of the cyclopropane ring (Scheme 1, equation 3). This behaviour is also consistent with a homologous enamine equivalent.…”
Section: Electron-rich Compounds: Cyclopropyl-amines Amides and Carbmentioning
confidence: 99%
See 2 more Smart Citations
“…35,36 As amines, they are also susceptible to undergo single-electron oxidation at the lone pair of the nitrogen atom, which triggers cleavage of the cyclopropane ring (Scheme 1, equation 3). This behaviour is also consistent with a homologous enamine equivalent.…”
Section: Electron-rich Compounds: Cyclopropyl-amines Amides and Carbmentioning
confidence: 99%
“…35 This process is thermodynamically favourable and depending on the substrates, the removal of a protecting group under transition-metal catalysed hydrogenation conditions can therefore be accompanied by extensive cyclopropanering opening (Scheme 4). 37,38,39,40,41,42,43,44,45 …”
Section: Transition-metal Catalysed Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuehne andK ing reported that treatment of the preformed enaminesw ith diazomethane in the presence of CuCl led to cyclopropylamines which aftert hermal hydrolysis gave alkylated carbonylc ompoundsa s am ixture of regioisomeric products. [45] It was reported that in the presence of Rh(II) complex the reaction of a-diazo ketones with vinyl ethers affordedc yclopropane derivatives which underwent ring-opening leading to 1,4-diketones. [46] Such cyclopropanes bearing bothe lectron-donating and electron-withdrawing groups were found to be easily cleaved.…”
Section: Mechanistic Considerationmentioning
confidence: 99%
“…[46] Such cyclopropanes bearing bothe lectron-donating and electron-withdrawing groups were found to be easily cleaved. [45][46][47][48][49] We have prepared acyclopropylamine derivative using areported methodology and subjected it to the developed reaction conditions (Scheme 4).…”
Section: Mechanistic Considerationmentioning
confidence: 99%